A method for preparing a high temperature resistant cladding of a quartz optical fiber with both strength and toughness
By preparing the BN/SiBCN-SiCw double cladding on the surface of the quartz fiber, the problem of insufficient service capacity of the existing quartz fiber cladding in high temperature and high humidity environments is solved, and the high temperature stability and toughness of the fiber are achieved, and the service life is extended.
Patent Information
- Application Number
- CN202410468519.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-18
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-04-18
AI Technical Summary
The existing quartz fiber cladding has insufficient service capacity in high temperature and high humidity environments, and the preparation process has problems such as damage to the fiber and degradation of thermal stability.
BN/SiBCN-SiCw double cladding was prepared on the surface of quartz optical fiber, and the BN inner cladding was prepared by chemical vapor deposition. The SiBCN-SiCw outer cladding was used to improve high temperature stability and enhance toughness.
It realizes the high temperature stability and toughness of quartz fiber in harsh environments, extends the service life of the fiber, and simplifies the preparation process.
Smart Images

Figure CN118459117B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical fiber reinforcement and toughening, and in particular to a method for preparing a quartz optical fiber cladding. Background Art
[0002] Quartz optical fiber has the characteristics of high light transmittance, wide spectral range, low loss, high bandwidth, and anti-electromagnetic interference. It is one of the most important transmission media in the field of optical communication and optical sensing, and is widely used in the fields of Internet, telecommunications, medical treatment, industrial control and sensing. However, due to the low strength and toughness of quartz optical fiber and its inability to resist the erosion of water vapor for a long time, its application in harsh environments such as high temperature, high humidity and high stress is restricted. The strength and toughness of quartz optical fiber are closely related to the preparation process of quartz optical fiber and the properties of the material itself. On the one hand, when quartz optical fiber is drawn out of the drawing furnace, there is a temperature gradient inside and outside the quartz optical fiber, which leads to stress gradient inside and outside and micro cracks on the surface, which eventually reduces the strength of the optical fiber. On the other hand, quartz optical fiber is mainly made of high-purity silica, and lacks strain energy release channels inside, which makes quartz optical fiber very brittle. Therefore, in order to improve the strength and toughness of optical fiber, enhance the service ability of optical fiber in harsh environments such as high temperature and high water and oxygen, expand the application range of optical fiber, and extend its service life, it is necessary to protect quartz optical fiber.
[0003] At present, one of the solutions to protect quartz optical fiber is to prepare a cladding on the surface of the quartz optical fiber to repair the micro cracks on the surface and improve the mechanical properties of the optical fiber. In order to achieve better protection of the optical fiber in harsh environments, the cladding of the optical fiber needs to meet the following requirements: a) the refractive index of the cladding material and the optical fiber should meet the total reflection requirement; b) the thermal expansion coefficient of the cladding material and the optical fiber should match well; c) the cladding material should have a high melting point, good thermochemical stability and mechanical stability. To meet the above conditions, the materials currently used to prepare the cladding of quartz optical fiber are mainly divided into metals, polymers and ceramics.
[0004] Metal cladding mainly uses aluminum, nickel, copper, gold, etc. These metal claddings have their own advantages and disadvantages: aluminum has a low melting point, and quartz optical fiber with aluminum cladding can generally only be used at around 400°C; quartz optical fiber clad with copper is difficult to use in a water and oxygen environment at 600°C; and gold cladding is too expensive. The metal cladding has a great influence on the macrobending loss characteristics of the optical fiber. In addition, in the process of preparing the metal cladding, there are problems of environmental pollution and inability to continuously coat over long distances. Polymer claddings include acrylic resin claddings, heat-resistant silicone claddings, and polyimide claddings. Fibers wrapped with polymers are beneficial to improving the toughness of the fibers. However, polymer claddings are difficult to serve for a long time in high-temperature environments above 350°C. Ceramic claddings are resistant to high temperatures and water and oxygen, and can protect quartz optical fibers at higher temperatures, but the brittleness of ceramic claddings still limits their application in optical fiber claddings. The current preparation of magnesium aluminate spinel ceramic cladding improves the mechanical, thermal and optical properties of optical fibers. However, the preparation temperature is relatively high for quartz optical fibers, which will cause damage to the optical fibers and seriously reduce the mechanical properties of quartz optical fibers. In addition, at around 900°C, due to the formation of an intermediate phase, its stability will drop significantly. Therefore, this cladding also has certain limitations at high temperatures.
[0005] In summary, the metal cladding has a low melting point and poor environmental adaptability, and has a great influence on the macrobending loss characteristics of the optical fiber; the polymer cladding is difficult to serve for a long time in a high temperature environment above 350°C; the ceramic cladding has a high preparation temperature, which will cause damage to the optical fiber, seriously reduce the mechanical properties of the quartz optical fiber, and reduce its stability at high temperatures.
[0006] The quartz optical fiber cladding service temperature reported in current research is relatively low or can only serve in relatively mild environments, and does not meet the requirements of combining strength and toughness and serving in harsh environments. Summary of the invention
[0007] In order to overcome the shortcomings of the prior art, the present invention proposes to prepare a BN / SiBCN-SiCw double cladding on the surface of a quartz optical fiber. Among them, the BN layer is an inner cladding, which is prepared by a chemical vapor deposition process. The inner cladding is used to heal the microcracks generated on the optical fiber surface during the preparation process; the outer cladding SiBCN has good high-temperature stability and is used to protect the BN inner cladding from the erosion of the external water and oxygen atmosphere, thereby improving its service capability at high temperatures. SiCw is introduced into SiBCN to enhance toughness and realize the strengthening and toughening of the optical fiber.
[0008] The technical solution adopted by the present invention to solve its technical problem is:
[0009] A method for preparing a high temperature resistant cladding of a quartz optical fiber with integrated strengthening and toughening, comprising the preparation of a boron nitride BN inner cladding and an outer cladding, comprising the following steps:
[0010] Preparation of Boron Nitride BN Inner Cladding:
[0011] Step 1: Remove the optical fiber cladding layer;
[0012] Use acetone to soften the cladding layer of the optical fiber in an ultrasonic bath. After the cladding layer is softened, remove the cladding layer, and then use alcohol and distilled water to clean the optical fiber in an ultrasonic bath in turn. After cleaning, place the optical fiber in an oven to dry;
[0013] Step 2: Fix the optical fiber to the graphite box and place it in the constant temperature zone of the boron nitride BN deposition furnace;
[0014] Put the dried optical fiber into a graphite box, fix one end of the optical fiber, make the other end of the quartz optical fiber free, and put the graphite box into the constant temperature zone of the boron nitride BN deposition furnace;
[0015] Step 3: Preparation of boron nitride BN deposition furnace reaction;
[0016] The pressure in the boron nitride BN deposition furnace is pumped down to below 1KPa, and argon gas is introduced at the same time, and then the temperature of the boron nitride BN deposition furnace is raised to 600-700°C, and the flow rate of the introduced argon gas is 50-200ml / min;
[0017] Step 4: Prepare BN cladding;
[0018] After the temperature of the boron nitride BN deposition furnace is stabilized, dilution gases BCl3, NH3, H2 and Ar are introduced; after BCl3, NH3, H2 and Ar react in the furnace of the boron nitride BN deposition furnace, the generated boron nitride BN is deposited on the surface of the quartz optical fiber to obtain a boron nitride BN cladding;
[0019] Step 5: Cooling of the boron nitride BN deposition furnace;
[0020] After the deposition is completed, the introduction of the reaction gas source is stopped, the heating system is turned off, and the furnace is cooled to room temperature, thereby obtaining an optical fiber with a boron nitride BN cladding that meets the total reflection condition;
[0021] Preparation of outer layer:
[0022] Step 6: preparing amino silicon carbide whiskers SiCw;
[0023] Mixing oleic acid with sodium lauryl sulfate to form a mixture;
[0024] Adding a mixture of oleic acid and sodium dodecyl sulfate into deionized water and mixing them evenly to prepare a mixed solution, wherein the mass ratio of the mixture of oleic acid and sodium dodecyl sulfate to deionized water is 20 to 100;
[0025] Adding silicon carbide whiskers SiCw into a mixed solution of oleic acid, sodium dodecyl sulfate and deionized water, wherein the mass ratio of the silicon carbide whiskers SiCw to the mixture of oleic acid and sodium dodecyl sulfate is 2:1;
[0026] After the silicon carbide whisker SiCw is added to a mixed solution of oleic acid, sodium dodecyl sulfate and deionized water, ethanol is added, and the ethanol plays a role of cleaning;
[0027] A mixed solution of silicon carbide whiskers SiCw, oleic acid, sodium dodecyl sulfate, deionized water and ethanol was cleaned in an ultrasonic cleaner for 30 minutes, and aminopropyl triethoxysilane APTES was added after cleaning, and then static aging was performed at a temperature of 60°C for 5 hours. The solid obtained after static aging for 5 hours was washed with anhydrous ethanol and deionized water respectively, and then dried in an electric heating blast drying oven to obtain SiCw with amino groups grown;
[0028] Step 7: Prepare the precursor solution
[0029] Polysilicon borazane PSNB and tetrahydrofuran THF are prepared into a silicon boron carbon nitrogen SiBCN precursor solution, and the obtained silicon boron carbon nitrogen SiBCN precursor solution is added to the SiCw growing amino group;
[0030] Step 8: Processing Boron Nitride (BN) Cladding Fiber
[0031] The boron nitride BN clad optical fiber prepared in step 5 is immersed in the silicon boron carbon nitrogen SiBCN precursor solution prepared in step 7 for 1 hour; then cured in argon at 120°C for 2 hours; after curing, the temperature is raised to 700°C; after heating, pyrolysis is performed in argon for 2 hours;
[0032] Step 9: Cool down to obtain a strengthened and toughened quartz fiber / BN / SiBCN-SiCw
[0033] After the pyrolysis, the mixture was cooled to room temperature at a cooling rate of 1°C / min to obtain a strengthened and toughened quartz optical fiber / BN / SiBCN-SiCw.
[0034] Furthermore, in step 4, the H2 flow rate is 50-150 ml / min;
[0035] The BCl3 gas flow rate is 10-30 ml / min;
[0036] The NH3 gas flow rate is 30-100 ml / min;
[0037] The Ar gas flow rate is 50-150 ml / min;
[0038] The deposition time is 1 to 20 hours.
[0039] Furthermore, in step 6, the mass ratio of oleic acid to sodium dodecyl sulfate is 0.1-3.
[0040] Furthermore, in step 6, the amount of aminopropyltriethoxysilane APTES added is: 1-3 ml;
[0041] Furthermore, in the step 7, in the silicon boron carbon nitride SiBCN precursor solution, the mass ratio of polysilicon borazane PSNB to tetrahydrofuran THF is 1:3.
[0042] Furthermore, in step 7, the mass ratio of the SiCw grown with amino groups to the sum of the SiCw grown with amino groups and the silicon boron carbon nitrogen SiBCN precursor solution is 0.5% to 5%.
[0043] Furthermore, in step 8, the boron nitride BN clad optical fiber is immersed in the precursor solution prepared in step 7 and then cured in argon at 120° C. for 2 hours, and then heated at a heating rate of 1 to 5° C. / min.
[0044] The beneficial effects of the present invention are as follows: the present invention proposes a method for preparing a high-temperature resistant cladding of a quartz optical fiber with integrated strengthening and toughness, wherein the BN inner cladding is prepared by chemical vapor deposition using BCl3-NH3-H2-Ar as raw materials; the SiBCN-SiCw outer cladding is prepared by a PDC polymer-derived ceramic method using a PSNB precursor as raw materials, a small amount of SiCw is added to a diluted precursor solution, and after being fully dispersed, the quartz optical fiber / BN is immersed therein, and solidified and pyrolyzed in argon to obtain quartz optical fiber / BN / SiBCN-SiCw.
[0045] The BN / SiBCN-SiCw double cladding prepared on the surface of the quartz optical fiber of the present invention is continuous and dense and has good interface bonding. Compared with bare optical fiber and quartz optical fiber / BN / SiBCN, quartz optical fiber / BN / SiBCN-SiCw has the best strength and toughness performance. In addition, the outer cladding of quartz optical fiber / BN / SiBCN-SiCw has excellent thermal stability at high temperature, which enhances the service ability of quartz optical fiber in harsh environments.
[0046] The BN inner cladding prepared by the inventive method is dense and uniform, ensuring that the optical signal does not leak during internal transmission, especially after the SiBCN-SiCw outer cladding is prepared on the surface of the quartz optical fiber / BN, the SiCw is dispersed in the SiBCN matrix through toughening mechanisms such as bridging and debonding, thus achieving the strengthening and toughening of the quartz optical fiber. In addition, the prepared SiBCN-SiCw outer cladding is resistant to water and oxygen and high temperature, which significantly improves the service ability of the quartz optical fiber in harsh environments, prolongs its service life, and has a simple process and good repeatability. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 : Stress-strain curves of quartz fiber, quartz fiber / BN / SiBCN and quartz fiber / BN / SiBCN-SiCw at room temperature; 1 is quartz fiber, 2 is quartz fiber / BN / SiBCN, and 3 is quartz fiber / BN / SiBCN-SiCw;
[0048] Figure 2 :Bending radius test of quartz fiber, quartz fiber / BN / SiBCN, quartz fiber / BN / SiBCN-SiCw, Figure 2 Among them, (a) is quartz fiber; (b) is quartz fiber / BN / SiBCN; (c) is quartz fiber / BN / SiBCN-SiCw;
[0049] Figure 3 :Surface morphology and cross-sectional morphology of quartz fiber / BN / SiBCN-SiCw, Figure 3 In the figure, (a) is the surface morphology; (b) is the cross-sectional morphology;
[0050] Figure 4 : Surface morphology and cross-sectional morphology of quartz optical fiber; Figure 4 In the figure, (a) is the surface morphology; (b) is the cross-sectional morphology;
[0051] Figure 5 It is a flow chart of the present invention. DETAILED DESCRIPTION
[0052] The technical solution adopted by the present invention to solve its technical problem is:
[0053] A method for preparing a high temperature resistant cladding of a quartz optical fiber with integrated strengthening and toughening, including the preparation of a BN inner cladding and an outer cladding, and the specific steps are as follows:
[0054] Preparation of BN inner cladding:
[0055] Step 1: Remove the optical fiber cladding layer;
[0056] Use acetone to soften the cladding layer of the optical fiber in an ultrasonic bath. After the cladding layer is softened, remove the cladding layer, and then use alcohol and distilled water to clean the optical fiber in an ultrasonic bath in turn. After cleaning, place the optical fiber in an oven to dry;
[0057] Step 2: Fix the optical fiber to the graphite box and place it in the constant temperature zone of the boron nitride BN deposition furnace;
[0058] Put the dried optical fiber into a graphite box, fix one end of the optical fiber, make the other end of the quartz optical fiber free, and put the graphite box into the constant temperature zone of the boron nitride BN deposition furnace;
[0059] Step 3: Preparation of boron nitride BN deposition furnace reaction;
[0060] The pressure in the boron nitride BN deposition furnace is pumped down to below 1KPa, and argon gas is introduced at the same time, and then the temperature of the boron nitride BN deposition furnace is raised to 600-700°C, and the flow rate of the introduced argon gas is 50-200ml / min;
[0061] Step 4: Prepare BN cladding;
[0062] After the temperature of the BN deposition furnace is stabilized, dilution gases BCl3, NH3, H2 and Ar are introduced; after BCl3, NH3 and H2 react in the furnace of the boron nitride BN deposition furnace, the generated boron nitride BN is deposited on the surface of the quartz optical fiber to obtain a boron nitride BN cladding, and the thickness of the boron nitride BN cladding is controlled by controlling the deposition time;
[0063] The H2 flow rate is 50-150 ml / min;
[0064] The BCl3 gas flow rate is 10-30 ml / min;
[0065] The NH3 gas flow rate is 30-100 ml / min;
[0066] The Ar gas flow rate is 50-150 ml / min;
[0067] The deposition time is 1 to 20 hours;
[0068] Step 5: Cooling of the boron nitride BN deposition furnace;
[0069] After the deposition is completed, the introduction of the reaction gas source is stopped, the heating system is turned off, and the furnace is cooled to room temperature, thereby obtaining an optical fiber with a boron nitride BN cladding that meets the total reflection condition;
[0070] Preparation of outer layer:
[0071] Step 6: preparing amino silicon carbide whiskers SiCw;
[0072] Mixing oleic acid and sodium dodecyl sulfate to prepare a mixture, wherein the mass ratio of oleic acid to sodium dodecyl sulfate is 0.1 to 3;
[0073] Adding a mixture of oleic acid and sodium dodecyl sulfate into deionized water and mixing them evenly to prepare a mixed solution, wherein the mass ratio of the mixture of oleic acid and sodium dodecyl sulfate to deionized water is 20 to 100;
[0074] Adding silicon carbide whiskers SiCw into a mixed solution of oleic acid, sodium dodecyl sulfate and deionized water, wherein the mass ratio of the silicon carbide whiskers SiCw to the mixture of oleic acid and sodium dodecyl sulfate is 2:1;
[0075] Add ethanol to the mixed solution containing silicon carbide whiskers SiCw, and the ethanol plays a role of cleaning;
[0076] The mixed solution of silicon carbide whiskers SiCw and ethanol was cleaned in an ultrasonic cleaner for 30 minutes, and then 1-3 ml of aminopropyltriethoxysilane APTES was added, and then static aging was performed at a temperature of 60°C for 5 hours. The solid obtained after static aging for 5 hours was washed with anhydrous ethanol and deionized water respectively, and then dried in an electric heating blast drying oven to obtain SiCw with amino groups grown;
[0077] Step 7: preparing a precursor solution;
[0078] Polysilicon borazane PSNB and tetrahydrofuran THF are prepared into a silicon boron carbon nitrogen SiBCN precursor solution in a mass ratio of 1:3, and the obtained precursor solution is added to the SiCw growing amino groups, and the mass ratio of the sum of the SiCw growing amino groups and the SiCw growing amino groups to the silicon boron carbon nitrogen SiBCN precursor solution is 0.5% to 5%;
[0079] Step 8: Processing the boron nitride BN cladding optical fiber;
[0080] The boron nitride BN clad optical fiber prepared in step 5 is immersed in the precursor solution prepared in step 7 for 1 hour; then cured in argon at 120°C for 2 hours; after curing, the temperature is increased at a heating rate of 1 to 5°C / min to 700°C; after heating, pyrolysis is performed in argon for 2 hours;
[0081] Step 9: Cool down to obtain a strengthened and toughened quartz fiber / BN / SiBCN-SiCw
[0082] After the pyrolysis, the mixture was cooled to room temperature at a cooling rate of 1°C / min to obtain a strengthened and toughened quartz optical fiber / BN / SiBCN-SiCw.
[0083] The present invention will now be further described with reference to examples and drawings:
[0084] A uniform and dense BN inner cladding was prepared on the surface of quartz optical fiber by chemical vapor deposition. Then, the quartz optical fiber / BN was placed in a SiBCN precursor solution containing SiCw, and the BN / SiBCN-SiCw double-cladding quartz fiber was obtained by impregnation, curing and pyrolysis.
[0085] The strength and toughness evaluation indicators of this experiment are completed through uniaxial tension test and bending test; the toughness of the sample is characterized by the bending radius, and the tensile strength of the sample can be calculated using the following formula:
[0086] σ=F / (πr2 )
[0087] Among them, F is the maximum load when the sample breaks, r is the radius of the sample; the cross-sectional area of the optical fiber composite material is estimated by observing the thickness through an electron microscope.
[0088] The stress-strain curves of the three samples are shown in Figure 1 As shown in the figure, quartz fiber / BN / SiBCN-SiCw has higher strength and strain, and the stress-strain of the three patterns is basically linear. Figure 2 (a, b, c) are the bending test results of quartz fiber, quartz fiber / BN / SiBCN, and quartz fiber / BN / SiBCN-SiCw, respectively. The bending radius of quartz fiber / BN / SiBCN-SiCw is the smallest. Table 1 summarizes the mechanical properties of the three samples, among which quartz fiber / BN / SiBCN-SiCw has the highest strength and the lowest modulus and bending radius. The strength of quartz fiber / BN / SiBCN is also much higher than that of bare quartz fiber. Compared with quartz fiber / BN / SiBCN, quartz fiber / BN / SiBCN-SiCw not only has increased strength, but also reduced modulus and bending radius. It can be seen that the addition of SiCw increases the crack propagation path, and the fracture and pull-out of SiCw also absorb more strain energy, thereby achieving the integration of optical fiber strength and toughness.
[0089] In addition, this experiment also compared and observed the surface morphology and cross-sectional morphology of quartz fiber / BN / SiBCN-SiCw and quartz fiber. Figure 3 The surface and cross-section of the quartz fiber. The surface morphology of the quartz fiber / BN / SiBCN-SiCw is as follows Figure 4 As shown in (a), it can be seen that the surface of the silica fiber / BN / SiBCN-SiCw cladding prepared by the PDC process is smooth and continuous without cracks; the cross-sectional morphology of the silica fiber / BN / SiBCN-SiCw is as follows Figure 4 As shown in (b), the thickness of the SiBCN-SiCw outer cladding is uniformly distributed along the radial direction of the quartz fiber, and there is no obvious agglomeration of SiCw on the SiBCN outer cladding. In addition, the holes on the upper side of the SiBCN-SiCw outer cladding cross section are formed due to the pulling out of SiCw.
[0090] Table 1 compares the mechanical properties of quartz fiber, quartz fiber / BN / SiBCN and quartz fiber / BN / SiBCN-SiCw at room temperature.
[0091] Table 1
[0092]
[0093] Process parameters of each embodiment:
[0094]
[0095]
Claims
1. A method for preparing a high temperature resistant cladding of a quartz optical fiber with integrated strengthening and toughening, characterized in that: The steps include preparation of a boron nitride BN inner cladding and an outer cladding, and are as follows: Preparation of BN inner cladding: Step 1: Remove the optical fiber cladding layer; Use acetone to soften the cladding layer of the optical fiber in an ultrasonic bath. After the cladding layer is softened, remove the cladding layer, and then use alcohol and distilled water to clean the optical fiber in an ultrasonic bath in turn. After cleaning, place the optical fiber in an oven to dry; Step 2: Fix the optical fiber to the graphite box and place it in the constant temperature zone of the boron nitride BN deposition furnace; Put the dried optical fiber into a graphite box, fix one end of the optical fiber, make the other end of the quartz optical fiber free, and put the graphite box into the constant temperature zone of the boron nitride BN deposition furnace; Step 3: Preparation of boron nitride BN deposition furnace reaction; The pressure in the boron nitride BN deposition furnace is pumped down to below 1KPa, and argon gas is introduced at the same time, and then the temperature of the boron nitride BN deposition furnace is raised to 600-700°C, and the flow rate of the introduced argon gas is 50-200ml / min; Step 4: Prepare BN cladding; After the temperature of the boron nitride BN deposition furnace is stabilized, dilution gases BCl3, NH3, H2 and Ar are introduced; after BCl3, NH3 and H2 react in the furnace of the boron nitride BN deposition furnace, the generated boron nitride BN is deposited on the surface of the quartz optical fiber to obtain a boron nitride BN cladding; Step 5: Cooling of the boron nitride BN deposition furnace; After the deposition is completed, the introduction of the reaction gas source is stopped, the heating system is turned off, and the furnace is cooled to room temperature, thereby obtaining an optical fiber with a boron nitride BN cladding that meets the total reflection condition; Preparation of outer layer: Step 6: preparing amino silicon carbide whiskers SiCw; Mixing oleic acid with sodium lauryl sulfate to form a mixture; Adding a mixture of oleic acid and sodium dodecyl sulfate into deionized water and mixing them evenly to prepare a mixed solution, wherein the mass ratio of the mixture of oleic acid and sodium dodecyl sulfate to deionized water is 20 to 100; Adding silicon carbide whiskers SiCw into a mixed solution of oleic acid, sodium dodecyl sulfate and deionized water, wherein the mass ratio of the silicon carbide whiskers SiCw to the mixture of oleic acid and sodium dodecyl sulfate is 2:1; After the silicon carbide whisker SiCw is added to a mixed solution of oleic acid, sodium dodecyl sulfate and deionized water, ethanol is added, and the ethanol plays a role of cleaning; A mixed solution of silicon carbide whiskers SiCw, oleic acid, sodium dodecyl sulfate, deionized water and ethanol was cleaned in an ultrasonic cleaner for 30 minutes, and aminopropyl triethoxysilane APTES was added after cleaning, and then static aging was performed at a temperature of 60°C for 5 hours. The solid obtained after static aging for 5 hours was washed with anhydrous ethanol and deionized water respectively, and then dried in an electric heating blast drying oven to obtain SiCw with amino groups grown; Step 7: Prepare the precursor solution Polysilicon borazane PSNB and tetrahydrofuran THF are prepared into a silicon boron carbon nitrogen SiBCN precursor solution, and the obtained silicon boron carbon nitrogen SiBCN precursor solution is added to the SiCw growing amino group; Step 8: Processing Boron Nitride (BN) Cladding Fiber The boron nitride BN clad optical fiber prepared in step 5 is immersed in the silicon boron carbon nitrogen SiBCN precursor solution prepared in step 7 for 1 hour; then cured in argon at 120°C for 2 hours; after curing, the temperature is raised to 700°C; after heating, pyrolysis is performed in argon for 2 hours; Step 9: Cooling down to obtain a strengthened and toughened integrated quartz optical fiber / BN / SiBCN-SiCw; After the pyrolysis, the mixture was cooled to room temperature at a cooling rate of 1°C / min to obtain a strengthened and toughened quartz optical fiber / BN / SiBCN-SiCw.
2. The method for preparing a high temperature resistant cladding of a quartz optical fiber with integrated strengthening and toughening according to claim 1, characterized in that: In step 4, the H2 flow rate is 50-150 ml / min; The BCl3 gas flow rate is 10-30 ml / min; The NH3 gas flow rate is 30-100 ml / min; The Ar gas flow rate is 50-150 ml / min.
3. The method for preparing a high temperature resistant cladding of a quartz optical fiber with integrated strengthening and toughening according to claim 1, characterized in that: In step 6, the mass ratio of oleic acid to sodium dodecyl sulfate is 0.1-3.
4. The method for preparing a high temperature resistant cladding of a quartz optical fiber with integrated strengthening and toughening according to claim 1, characterized in that: In the step 6, the amount of aminopropyltriethoxysilane APTES added is 1 to 3 ml.
5. The method for preparing a high temperature resistant cladding of a quartz optical fiber with integrated strengthening and toughening according to claim 1, characterized in that: In the step 7, in the silicon boron carbon nitride SiBCN precursor solution, the mass ratio of polysilicon borazane PSNB to tetrahydrofuran THF is 1:
3.
6. The method for preparing a high temperature resistant cladding of a quartz optical fiber with integrated strengthening and toughening according to claim 1, characterized in that: In the step 7, the mass ratio of the SiCw grown with amino groups to the sum of the SiCw grown with amino groups and the silicon boron carbon nitrogen SiBCN precursor solution is 0.5% to 5%.
7. The method for preparing a high temperature resistant cladding of a quartz optical fiber with integrated strengthening and toughening as claimed in claim 1, characterized in that: In the step 8, the boron nitride (BN) clad optical fiber is immersed in the silicon boron carbon nitride (SiBCN) precursor solution prepared in step 7 and then cured in argon at 120° C. for 2 hours, and then heated at a heating rate of 1 to 5° C. / min.
Citation Information
Patent Citations
High-temperature-resistant wave-transparent silicon nitride fiber-reinforced composite material and preparation method thereof
CN104261850A
Nitride fiber reinforced composite material and preparation method and application thereof
CN113735596A